Primary testicular diffuse large B-cell lymphoma: Case series. Issue 12 (March 2020) - Wang, Qi; Zheng, Dafang; Chai, Damin; Wu, Shiwu; Wang, Xiaolin; Chen, Shaonan; Wu, Linhui; Cao, Ruoxue; Tao, Yisheng
Abstract: Rationale: Primary testicular lymphoma (PTL) is a rare type of extranodal non-Hodgkin's lymphoma (NHL). Although data of PTL in patients with diffuse large B-cell lymphoma (DLBCL) are accumulating, there are still patients respond poorly to prognosis. Patient concerns: All patients had disease of the DLBCL subtype and those patients had primary involvement of the testis. In our studies, eleven patients had stage I/II disease, and 3 patients had advanced disease with B symptoms. Four patients exhibited a MYC+, BCL2+, and BCL6- expression pattern, 4 patients had a MYC+, BCL6+, and BCL2- expression pattern, and 3 patients had a MYC+, BCL2+, and BCL6+ expression pattern. Additionally, 43% (7/16) of PT-DLBCL patients had a germinal center B-cell-like (GCB) phenotype, while the others had a non-GCB phonotype. Diagnoses: In our case, most patients presented with unilateral painless scrotal swelling and the enlargement of the testicles in the first examination. After hospitalization, all patients underwent preoperative imageological examination of the testis and epididymis and postoperative revealed that all patients were the diffuse infiltration of a large number of anomalous lymphocytes. In addition, no invasion of other sites was observed within 3 months after diagnosis. Interventions and outcomes: Underwent orchiectomy on the affected side was performed by urologists after all patients were diagnosed with PTL. Meanwhile, some patients received at least one course of chemotherapy, or received postoperative combined RT and chemotherapy. Because of it particularity, nineteen instances of lymph node region involvement were discovered in 12 patients since the operation. Lessons: PT-DLBCL has unique biological characteristics, and its treatment modalities are becoming increasingly standardized. In the future, systematic interventions need to be actively considered in the early stages of PTL.